Silica-Based Nanoframeworks Involved Hepatocellular Carcinoma Theranostic - Liu, Yunxi; Chen, Yue; Fei, Weidong; Zheng, Caihong; Zheng, Yongquan; Tang, Miao; Qian, Ying; Zhang, Xiao; Zhao, Mengdan; Zhang, Meng; Wang, Fengmei (Frontiers in Bioengineering and Biotechnology, 2021)
Silica-based nanoframeworks have been extensively studied for diagnosing and treating hepatocellular carcinoma (HCC). Several reviews have summarized the advantages and disadvantages of these nanoframeworks and their use as drug-delivery carriers. Encouragingly, these nanoframeworks, especially those with metal elements or small molecular drugs doping into the skeleton structure or modifying onto the surface of nanoparticles, could be multifunctional components participating in HCC diagnosis and treatment rather than functioning only as drug-delivery carriers. Therefore, in this work, we described the research progress of silica-based nanoframeworks involved in HCC diagnosis (plasma biomarker detection, magnetic resonance imaging, positron emission tomography, photoacoustic imaging, fluorescent imaging, ultrasonography, etc.) and treatment (chemotherapy, ferroptotic therapy, radiotherapy, phototherapy, sonodynamic therapy, immunotherapy, etc.) to clarify their roles in HCC theranostics. Further, the future expectations and challenges associated with silica-based nanoframeworks were highlighted. We believe that this review will provide a comprehensive understanding for researchers to design novel, functional silica-based nanoframeworks that can effectively overcome HCC.